Defining lifestyle migration - Torkington, Kate (2010)
This paper seeks to provide a conceptual framework for studying migration to the Algarve by Northern Europeans. ‘Lifestyle migration’ is suggested as a generic term for this trend, which is part of a recent but flourishing global social phenomenon. I also point to the glaring gap in the literature as far as empirical studies based in the Algarve are concerned, and make suggestions for a research agenda.